Comparing clinical and economic outcomes of biologic and conventional medications in postmenopausal women with osteoporosis. Issue 5 (9th June 2015) - Hernandez, Inmaculada; Zhang, Yuting
Abstract Rationale, aims and objectives Biologics are substantially more expensive than their conventional counterparts but it is unclear whether extra costs deliver better health outcomes. We compare clinical and economic outcomes between teriparatide (monthly costs 1120) and bisphosphonates (monthly costs 14) among postmenopausal women with osteoporosis. Methods From a 5% random sample of Medicare beneficiaries, we selected women newly diagnosed with osteoporosis between 1 January 2007 and 31 December 2011 and who initiated teriparatide or bisphosphonates after the diagnosis. We followed them up until one of these events: switching osteoporosis treatment, death, or the end of study period ‐ 31 December 2011. Clinical outcomes included hip fracture, vertebral fracture, fracture of radius, ulna or carpal bones, other upper limb fractures, other lower limb fractures and any fracture. Economic outcomes included medical costs, pharmacy costs, and total costs associated with osteoporosis. Using conventional propensity score, high‐dimensional propensity score and instrumental variable analysis, we constructed Cox proportional hazards models to evaluate the risk of fracture and two‐part models to compare costs. Results Teriparatide users had higher risk of fracture and higher costs, compared with similar bisphosphonates users. The hazard ratios of fracture for teriparatide relative to bisphosphonates ranged from 1.37 to 2.12, depending on methods. There was no difference in the risk of hip fracture between treatment groups. Total annual costs related to osteoporosis were between 2733 and 3352 higher for teriparatide users. Conclusions The biological agent, teriparatide, is more expensive yet less effective than conventional treatment, bisphosphonates.